Penerapan Naskah Kuno dan Pemanfaatannya untuk Pengembangan Wisata Religi Ziarah di Surau Simaung Kabupaten Sijunjung - Pramono Pramono; Muchlis Awwali; Donny Eros; Rafiq Gusly Abdul Razaq; Surya Selfika; Nur Ahmad Salman Herbowo (Warta Pengabdian Andalas, 2022)
Most Minangkabau manuscripts are collections of traditional mosques called "Surau Tarekat" in West Sumatra. Some of them are always crowded with congregations for pilgrimage. One of them is Surau Simaung, Nagari Sijunjung, Sijunjung Regency, and West Sumatra. The development of ancient manuscripts in Surau Simaung's collection can be relevant to present and future life. The development of ancient manuscripts as a source of value is not meant to go backwards but rather to pick up existing ones to be pushed forward as a source of creative economic development. This manuscript, it is hoped that it will support the development of religious pilgrimage tourism in West Sumatra, which has not been appropriately managed and maximally until now. This program was designed to find and explore the potential of Minangkabau manuscripts which can be developed as a creative industry. Implementing community service was training for students studying at Surau Simaung called "Pakiah" to produce unique souvenirs from the manuscripts. Producing text editions of manuscripts containing biographies of Tarekat scholars and their teachings can revive the creative industry, especially the publishing sector and the engineering of Batik motif illumination. In conclusion, Pakiah has the skills in making Batik and screen printing with illuminated motifs of ancient manuscripts in the Surau Simaung collection and can promote them.